Effects of fences and fence gaps on the movement behavior of three southern African antelope species - Hering, Robert; Hauptfleisch, Morgan; Kramer-Schadt, Stephanie; Stiegler, Jonas; Blaum, Niels (Frontiers in Conservation Science, 2022)
Globally, migratory ungulates are affected by fences. While field observational studies reveal the amount of animal–fence interactions across taxa, GPS tracking-based studies uncover fence effects on movement patterns and habitat selection. However, studies on the direct effects of fences and fence gaps on movement behavior, especially based on high-frequency tracking data, are scarce. We used GPS tracking on three common African antelopes (Tragelaphus strepsiceros, Antidorcas marsupialis, and T. oryx) with movement strategies ranging from range residency to nomadism in a semi-arid, Namibian savanna traversed by wildlife-proof fences that elephants have regularly breached. We classified major forms of ungulate–fence interaction types on a seasonal and a daily scale. Furthermore, we recorded the distances and times spent at fences regarding the total individual space use. Based on this, we analyzed the direct effects of fences and fence gaps on the animals’ movement behavior for the previously defined types of animal–fence interactions. Antelope-fence interactions peaked during the early hours of the day and during seasonal transitions when the limiting resource changed between water and forage. Major types of ungulate–fence interactions were quick, trace-like, or marked by halts. We found that the amount of time spent at fences was highest for nomadic eland. Migratory springbok adjusted their space use concerning fence gap positions. If the small home ranges of sedentary kudu included a fence, they frequently interacted with this fence. For springbok and eland, distance traveled along a fence declined with increasing utilization of a fence gap. All species reduced their speed in the proximity of a fence but often increased their speed when encountering the fence. Crossing a fence led to increased speeds for all species. We demonstrate that fence effects mainly occur during crucial foraging times (seasonal scale) and during times of directed movements (daily scale). Importantly, we provide evidence that fences directly alter antelope movement behaviors with negative implications for energy budgets and that persistent fence gaps can reduce the intensity of such alterations. Our findings help to guide future animal–fence studies and provide insights for wildlife fencing and fence gap planning.